2015
DOI: 10.1002/smll.201501788
|View full text |Cite
|
Sign up to set email alerts
|

Mesostructured Composite Materials with Electrically Tunable Upconverting Properties

Abstract: A promising approach of designing mesostructured materials with novel physical behavior is to combine unique optical and electronic properties of solid nanoparticles with long-range ordering and facile response of soft matter to weak external stimuli. Here, orientationally ordered nematic liquid crystalline dispersions of rod-like upconversion nanoparticles are designed, practically realized, and characterized. Boundary conditions on particle surfaces, defined through surface functionalization, promote spontan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 41 publications
2
49
0
1
Order By: Relevance
“…Considering the luminescence from a collection of ions doped in solids, it can be speculated that the excitation polarization dependence represents a statistic performance of individual ions. If the transition dipoles of the doping ions are randomly oriented, as encountered in amorphous or polycrystalline structures, the excitation polarization selectivity and the emission polarization anisotropy would diminish . However, in monocrystalline lattices, where the local polyhedrons hosting the luminescence centers are well organized, the luminescence from a collection of ions could still exhibit excitation polarization selectivity, as the normalΓmnormalΓn transition dipoles have a limited number of orientations and are oriented in relation to the principal axes of the local coordination polyhedron center of luminescence (Figure a‐b) .…”
Section: Optical Responses Of Upconversion Systems To External Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the luminescence from a collection of ions doped in solids, it can be speculated that the excitation polarization dependence represents a statistic performance of individual ions. If the transition dipoles of the doping ions are randomly oriented, as encountered in amorphous or polycrystalline structures, the excitation polarization selectivity and the emission polarization anisotropy would diminish . However, in monocrystalline lattices, where the local polyhedrons hosting the luminescence centers are well organized, the luminescence from a collection of ions could still exhibit excitation polarization selectivity, as the normalΓmnormalΓn transition dipoles have a limited number of orientations and are oriented in relation to the principal axes of the local coordination polyhedron center of luminescence (Figure a‐b) .…”
Section: Optical Responses Of Upconversion Systems To External Stimulimentioning
confidence: 99%
“…Additionally, they found that the aspect ratio showed neglectable effect on the polarization anisotropy of upconversion luminescence, which is different from micropolarized spectroscopy of semiconductor systems where the aspect ratio is a critical factor which affects the polarization property of particles . In addition, it was reported that the residual polycrystallinity present in the UCNPs limited the polarization anisotropy of the individual particles . Aligned arrays of upconversion nanorods were demonstrated to exhibit polarization anisotropy, while randomly oriented nanorods would average out the anisotropy …”
Section: Optical Responses Of Upconversion Systems To External Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…[30] A more detailed description for the surface functionality procedure is provided in the Supporting Information. [30] A more detailed description for the surface functionality procedure is provided in the Supporting Information.…”
Section: Doi: 101002/adom201600956mentioning
confidence: 99%
“…[27,28] In their cases, UCNPs were capable of efficiently converting low-energy NIR light to UV or visible radiation, triggering the photoisomerization or photocyclization process of light-driven switches, thereby leading to the pitch change or handedness inversion of helical superstructures. However, apart from the polarized luminescence tuning of upconversion nanorod in LC media, [30] almost no attention has been focused on using LC alignment for tuning the luminescence intensity of UCNPs in LC host.In this study, for the first time, we propose a facile but effective strategy to modulate the luminescence intensity of UCNPs in the liquid crystal network (LCN) composite films and further to fabricate upconversion luminescence patterns. [29] Similarly, the doped UCNPs converted NIR light to UV radiation, triggering the trans-cis photoisomerization of the azotolane units and an alignment change of the LC molecules.…”
mentioning
confidence: 99%